Adaptation of the Novel Negeri 5 Menara into a Feature Film - Anwar, Anwar; Jatmiko, Henry Trias Puguh; Prastiwi, Liyana Dian (Melekliterasi Press, 2025)
This study aims to describe the adaptation of the novel Negeri 5 Menara into a feature film. The research method used is a qualitative descriptive approach. The data consists of excerpts from the novel Negeri 5 Menara and transcripts from the film Negeri 5 Menara. The data was collected using the techniques of reading, listening and note-taking, coding, and then validated using triangulation theory. After that, it was analysed using adaptation of the Novel Negeri 5 Menara into a Feature Film